The Effect of Administration of Morage Brownies on Increasing Hemoglobin Levels in Pregnant Women - Endah Yulianingsih; Thumartony Thaib Hiola; Gabriella Dwi Meifani (Universitas Muhammadiyah Semarang, 2022)
Data of Provincial Health Agency in 2017 revealed that there were 899 pregnant mothers with anemia while the second-highest number recorded in Gorontalo City for 161 people. Additionally, data of Health Agency of Gorontalo City in 2018 found Puskesmas Dungingi as the highest spot with anemia for 64 people. The research aimed to analyze the influence of moringa brownies towards the increase of hemoglobin level at pregnant mothers in the working area of Puskesmas Dungingi of Gorontalo City in 2019. Research methodology: it applied pre-experimental research with one group pre-post test approach. The population of this research was 50 pregnant mothers in trimester II and II. The sampling applied purposive sampling so that it obtained 30 people as samples. The independent variable was moringa brownies, and the dependent variable was the hemoglobin level. The finding of research: the hemoglobin level of respondents who consumed moringa brownies increased for 66,7% and those who did not increase was 33,3%. The data analysis used Mc Nemar test, which achieved p-value for 0,002 < 0,05. Conclusion: there was an influence of moringa brownies towards the increase of hemoglobin level at pregnant mothers.